The Malaysian seas: variation of sea level observed by tide gauges and satellite altimetry - Omar, Kamaludin (2005)

(untitled)
Since a decade, satellite altimetry has demonstrated its capability in measuring temporal change of the global mean sea level with precision better than 1 mm/year. In altimetry data processing, the recently updated environmental and geophysical corrections were applied. The analysis of Topex data presented here is based on monthly averages using GOT00.2b ocean tide model. Sea level trends are estimated from 1.5 to 8.9 mm/year using two decades of tide gauges observations along coastal of Malaysia. Comparison of 1o x 1o areas at the tide gauge locations nearby Topex track clearly show good agreement in pattern and trend of sea level variations. Here, sea level variations for four areas in the Malaysian Seas have been investigated using ten years of Topex altimetry data. The time series of dynamic sea surface elevation clearly show El Nino effect on the end of 1997 and sea level rising in the Malaysian Seas. Linear terms of sea level variation for those areas are estimated at rates between 6.3-14.7 mm/year.